2001
DOI: 10.2139/ssrn.289060
|View full text |Cite
|
Sign up to set email alerts
|

A Yen is Not a Yen: TIBOR/LIBOR and the Determinants of the 'Japan Premium'

Abstract: Pricing in the Euroyen market is based on LIBOR, the London Interbank Offered Rate, set at 11am London time or TIBOR, the Tokyo Interbank Offered Rate, set at 11am Tokyo time. Since the TIBOR panel is dominated by Tokyo city banks while the LIBOR panel is dominated by non-Japanese banks, the changing TIBOR-LIBOR spread reflects the credit risk associated with Japanese banks or the "Japan premium." In this paper, we investigate the determinants of this "Japan premium." The spread is modeled as a function of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Various observations were found in this regression analysis. Covrig et al (2004) conducted studies on TIBOR/LIBOR and the determinants of the 'Japan Premium'. The study indicated that the changing TIBOR-LIBOR spread affects credit risk associated with Japan premium.…”
Section: Commodity Indices Risk and Return Analysis Against Libor Benmentioning
confidence: 99%
“…Various observations were found in this regression analysis. Covrig et al (2004) conducted studies on TIBOR/LIBOR and the determinants of the 'Japan Premium'. The study indicated that the changing TIBOR-LIBOR spread affects credit risk associated with Japan premium.…”
Section: Commodity Indices Risk and Return Analysis Against Libor Benmentioning
confidence: 99%
“…In a similar fashion, skewness risk in swaps can be measured using stock market data. In this paper we extract the ideas of skewness risk from a number of studies relevant for swap markets (Adrian & Rosenberg, 2008;Batten & Covrig, 2004;Covrig et al, 2004;Ito & Harada, 2004;and Nishioka & Baba, 2004). Adrian and Rosenberg's (2008) explanation is applicable to any financial product, with skewness risk providing a measure of the tightness of financial constraints.…”
Section: Skewness Risk In Swapsmentioning
confidence: 99%
“…Ignoring the dynamics of the correlation structure between underlying interest rates can also lead to serious errors in the pricing model and hedging decisions. Covrig, Low, and Melvin (2004) and Batten and Covrig (2004) show that skewness risk is present in the short end of the Japanese yield curve, due to pricing distortions associated with the difference between TIBOR and LIBOR interest rates (the Tokyo Interbank Offer Rate and the London Interbank Offer Rate respectively) for unsecured deposits. Thus, determining whether skewness risk is also priced into yen swap spreads is especially important for those market participants who use TIBOR, or LIBOR, based futures contracts to arbitrage, or hedge, the floating rate side of yen interest rate swaps.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 shows these two rates since the mid 1990s. Peek and Rosengren (2001) and Corvig, Low, and Melvin (2004), risks in the banking sector in Tokyo caused interest rates on inter-bank loans to rise in Tokyo compared with London. In other words, Tibor rates rose relative to Libor rates, as shown in Figure 10 and Figure 11, which shows the Tibor-Libor spread for three-month loans.…”
Section: Developments In Other Countriesmentioning
confidence: 99%